Beyond Administrative Compliance: Operationalizing the Spirituality Requirement for Notary Appointment under Indonesia's Notary Law - Aziwarti; Machdaliza Masri; Novrida Fauziyah Nasution; Ajasri (Arkus, 2024)
The appointment of notaries in Indonesia requires "devotion to the One Almighty God" (piety) under Article 3(b) of the Notary Law (UUJN), yet this transcendental prerequisite is frequently reduced to a bureaucratic formality of document submission. This study examined how the spirituality requirement is operationalized by state authorities and supervisory councils, and whether perceived operationalization predicts the ethical accountability of newly appointed notaries. A convergent mixed-methods socio-legal design was used in a Malay-Islamic customary province of western Indonesia, with specific locations masked as an urban cluster ("Kota Alpha") and a semi-urban cluster ("Kabupaten Beta"). The qualitative core comprised in-depth interviews with nine key informants analyzed by the Miles-Huberman-Saldana model; a complementary survey of 128 notaries and stakeholders (64 per cluster) used validated Likert scales (Cronbach's α 0.80-0.90). Administrative formalism was higher in the urban cluster (3.39 vs 2.85; d=1.10; p<0.001), whereas community moral control was markedly higher in the semi-urban cluster (3.47 vs 2.28; d=2.31; p<0.001), as was ethical accountability orientation (3.46 vs 2.78; d=1.16; p<0.001). In multiple regression (R²=0.434; F(5,122)=18.70; p<0.001), community moral control was the strongest predictor of accountability (β=0.505; 95% CI 0.253-0.610; p<0.001) and administrative formalism a negative predictor (β=-0.204; p=0.011), while region became non-significant once these were controlled, indicating the regional gap was channelled through living-law moral control. The findings reveal an "illusion of spiritual measurement" in which the state substitutes document-based compliance for substantive verification. Transforming transcendental spirituality into measurable professional-ethics indicators through community-based background checks is recommended.